PEMBERIAN ASUPAN CAIRAN MENURUNKAN KEJADIAN KONSTIPASI DAN KONSISTENSI FESES PADA PASIEN IMOBILISASI AKIBAT FRAKTUR - Rosliany, Nia (Jurnal Kesehatan Holistic, 2017)
Patients often experience a decrease in mobility as a result of the fracture. Prevention of constipation is needed to reduce the complications of immobilization. This study aimed to determine the effect of drinking 2000 ml water regularly and scheduled to prevent constipation. This study applied a quasi-experimental design with a post-test only non-equivalent control group on 28 subjects allocated to intervention group (14 subjects) and control group (14 subjects). The intervention group drink 8 times administration of 1 cup of water (250 ml). The result showed there was significant differences in the incidence of constipation with p value = 0.023 and stool consistency with p value = 0.009 (p value < 0.05) between the groups. Therefore, drinking 2000 ml water per day regularly and scheduled can prevent constipation and produce the ideal stool consistency. Further study might be needed with more sample and homogens type of fracture.